Solitary Fibrous Tumor of the Mediastinum: A Rare Clinical Entity and Review of the Literature - Sahni, Manish; Sisodiya, Anula; Shah, Apurva; Devgarha, Sanjeev (Asian Pacific Journal of Cancer Care, 2024)
Solitary fibrous tumor (SFT) is an uncommon mesenchymal tumor, generally exhibiting indolent clinical behavior compared to its malignant counterpart. There are very few reported cases of extrapleural malignant SFT arising from the mediastinum. This report presents a rare case of solitary fibrous tumor originating in the mediastinum and reviews the relevant literature on this entity.